1999
DOI: 10.1023/a:1008927222081
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The structural changes of two calcium-sodium metaphosphate glasses during its dissolution in simulated body fluid (SBF) have been analyzed by Fourier transform Raman spectroscopy (FT-Raman), scanning electron microscopy (SEM) and environmental scanning electron microscopy (ESEM). The results showed that no structural changes could be detected during the first week of dissolution. However, after approximately 4 weeks of dissolution the analysis of the glass surface revealed the presence of a thin orthophosphate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(10 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…This is due to the expected strong ionic cross-linking in the phosphate network structure from the inclusion of Mg 2+ , Zn 2+ and Ca 2+ cations and their respective charge-to-size ratios (0.0232, 0.0227 and 0.0175). The network structure would then be more capable of suppressing the onset of crystallisation in line with previous results [20, 33, 36, 37]. However, previous studies have also shown that increased network stability is associated with a higher T g due to the increased energy required to fracture the structural bonds that contradicts the comparatively low T g found in these results.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This is due to the expected strong ionic cross-linking in the phosphate network structure from the inclusion of Mg 2+ , Zn 2+ and Ca 2+ cations and their respective charge-to-size ratios (0.0232, 0.0227 and 0.0175). The network structure would then be more capable of suppressing the onset of crystallisation in line with previous results [20, 33, 36, 37]. However, previous studies have also shown that increased network stability is associated with a higher T g due to the increased energy required to fracture the structural bonds that contradicts the comparatively low T g found in these results.…”
Section: Discussionsupporting
confidence: 82%
“…This indicated the precipitation of compounds out of solution due to the super saturated conditions of the media and the ions released during glass fibre dissolution [36]. The handling of fibres also became increasingly difficult after 48 h due to increasing brittleness.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…P is a macronutrient essential for physiological functions such as skeletal development, mineral metabolism and cell signaling [ 27 , 28 ], and dietary intake of B plays important roles in bone formation and maintenance [ [29] , [30] , [31] ]. PBG have been formed with good bioactivity and biocompatibility and have been proposed for bone repair and reconstruction [ 32 , 33 ]. Similarly, BBG have been shown to promote the osteogenic differentiation of human mesenchymal stem cells in vitro [ 39 ], used to treat osteomyelitis in a rabbit model in vivo [ 34 ], and employed to repair calvarial defects in mice [ 42 , 43 ].…”
Section: Introdctionmentioning
confidence: 99%
“…13,14 Thus, phosphate glasses have been studied in various biomedical applications, especially for use in bone repair and reconstruction. 15 Apart from their biological properties, phosphate glasses are also of great interest due to their easy processing, excellent thermo-mechanical and chemical properties, homogeneity, good thermal stability, and excellent optical properties, such as high transparency in the UV-Visible-Near-Infrared (UV-Vis-NIR) region. [16][17][18][19][20] Besides, phosphate glasses allow high rare-earth (RE) ions solubility.…”
mentioning
confidence: 99%